RmCP, a cerato-platanin protein from Rigidoporus microporus, induces defense responses during interaction with Hevea brasiliensis - Maiden, Nor Afiqah; Atan, Safiah; Mui-Yun, Wong (Frontiers in Microbiology, 2025)
IntroductionThe rubber tree (Hevea brasiliensis) is susceptible to various fungal pathogens with Rigidoporus microporus being one of the most harmful. This fungus causes white root disease in rubber trees which can potentially lead to massive tree losses if left untreated. The use of elicitor proteins in enhancing host plant resistance represents a sustainable approach for disease control by reducing the use of chemical fungicides. Although cerato-platanin proteins (CPs) are recognized elicitors in many pathosystems, CP from R. microporus has not been functionally characterized, leaving its role in rubber–pathogen interactions unknown.MethodsThe coding sequence of the CP homolog RmCP was heterologously expressed in Escherichia coli and purified to homogeneity by two-steps purification method, namely, affinity and size-exclusion chromatography. Bioactivity was assessed by infiltrating micromolar concentrations of RmCP into leaves of the host (H. brasiliensis) and a model non-host (Nicotiana tabacum).ResultsCell death (Trypan blue), reactive-oxygen species (DAB/NBT), callose deposition (aniline blue) and transcription of four defense-related genes (HbCDPK5, HbMAPK, HbPR3, HbEDS1) were monitored over 72 h. Purified RmCP migrated as a single band between 11 and 17 kDa band. Infiltration induced localized necrosis in N. tabacum within 48 h and in detached rubber leaves within 72 h. Both hosts accumulated H₂O₂ and O₂−, and deposited callose. Additionally, significant up-regulation of HbCDPK5 and HbMAPK (early signaling), followed by strong induction of downstream effector genes, HbPR3 and HbEDS1 was observed in H. brasiliensis. These findings identify RmCP as the first basidiomycete CP shown to activate multilayer innate immunity in a latex-producing perennial.ConclusionThe study extends the functional spectrum of the CP family beyond ascomycete models and provides a biochemically defined platform for developing protein-based priming agents to combat white-root disease in rubber plantations.